Limb Transplantation and Targeted Reinnervation: A Practical Comparison - Agnew, Sonya Paisley; Ko, Jason; De La Garza, Mauricio; Kuiken, Todd; Dumanian, Gregory (Journal of Reconstructive Microsurgery, 2012)
Limb transplantation and targeted reinnervation are complimentary but very different approaches for restoring function to an upper limb amputee. This article reviews the advantages and limitations of both of these procedures, and highlights the reconstructive obstacles in the treatment of upper limb amputees.
Keywords: limb transplantation; targeted reinnervation; comparison